The Relationship Between The Level Of CALIS Knowledge And Satisfaction Among International Students: A Case Study At Library Of Central China Normal University (CCNU) - Siti Aminah (Jurnal IPI (Ikatan Pustakawan Indonesia), 2020)
This research is about the relationship between the level of CALIS knowledge and satisfaction among international students: a case study at Library of Central China Normal University (CCNU). This research used quantitative approach that divided in two analyses such as descriptive statistic and inferential statistic. In the descriptive statistic, this study aims to describe the demographic information such as gender, age, major, country, and level of education. In the inferential statistic, the study obtains the relationship between knowledge of users and users satisfaction, then it obtains the effect of users knowledge and users satisfaction. The finding of this study has showed CALIS in CCNU library need to be further introduced to the international students. International students lacked knowledge of CALIS, therefore they didn’t know how to properly access CALIS. After the author conducted a survey to international students, the author found the students have the basic level of knowledge of CALIS, but when it comes to accessing the thesis, they have a constraint due to the Chinese language. Therefore, the information that they needed was not quickly available. In conclusion, the results of user accessibility indicated when knowledge of CALIS increased, the level of user satisfaction also increased. Likewise, when the user lacked knowledge, the level of user satisfaction also lacked.